Comparison between Mammography and Breast Ultrasound in the Detection of Breast Cancer in Dense Breast Tissue among a Sample of Iraqi Women - Abdulwahid, hiba mohammed (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Breast cancer is the most common cancer reported in women worldwide . In Iraq, it is the  most common registered malignancy. Mammography plays a major role in  the early detection of breast cancers. Dense breast parenchyma has been reported to be the most important inherent factor that limits  depiction of breast cancer on mammogram, and often needs supplementary breast ultrasound for complete assessment. Objectives: To evaluate and compare the diagnostic performance of mammography and ultrasound in thedetection of breast cancer in dense breast tissue.Patients and methods: A record review study was performed in the Oncology Teaching Hospital/ MedicalCity from April 2018 to December 2018. The study included forty five females, who attended the MainReferral Center for Early Detection of Breast Tumors during 2017 and 2018 were diagnosed with breast  cancer histopathologically . They had dense breast tissues on mammography (either heterogeneously densebreast tissue i.e . category C or extremely dense breast tissue i.e. category D). All patients underwent  subsequent breast ultrasound . Their information including the mammogram findings, breast ultrasound,fine needle aspiration (FNA) and biopsy results were reviewed analyzed and compared.Results:Twenty four patients (53.3%) had heterogeneously dense breast tissue (ACR category C) and 21patients (46.6%) had extremely dense breast tissue (ACR category D). The mammogram detected 36 from 45breast cancers (80%) while 9 (20%) were not detected by mammogram, so the mammogram had a detectionrate of breast cancer of 80% in mammographically dense breast, while breast ultrasound had higher  detection rate of about 97.7% .The sensitivity of mammography in extremely dense breast tissue was about 71% and in heterogeneously dense breast was about 87% while ultrasound had shown a higher sensitivitywith increasing tissue density (98% vs. 100%).Conclusion: Breast cancer can be easily obscured and missed in mammographically dense breast tissue dueto overlapping surrounding fibroglandular tissue and additional complementary breast ultrasound is highlyrecommended for a thorough evaluation and to depict mammographically occult breast carcinoma.